The Significance Key of Intellectual Capital To Increase Financial Performance, Firm's Growth, and Market Value - Wawan Sadty Nugroho; Gudono Gudono (The Indonesian Journal of Accounting Research, 2018)
Abstract : The purpose of this study is to examine the contact between intellectual capital and financial performance, firm’s growth, and market value also on high-tech industry, low-tech industry, and telecommunication companies. Another contribution of this study is to investigate is there any intellectual capital differences between each company’s sectors. Value Added Intellectual capital (VAICTM) method by Pulic (1998, 1999, 2000, 2003) is used to verify the effect of intellectual capital on financial performance, firm's growth, and market value. By using purposive sampling method in 5 years period from 2010 to 2014, obtained 45 sample of the high-tech industry, 185 sample of low-tech industry, and 25 sample of telecommunication companies. Partial Least Square (PLS) and one-way ANOVA are used in this study to investigate the empirical causalities of each variable. The results of the analysis indicate that intellectual capital has a positive effect on financial performance. The results also revealed that there are intellectual capital differences in each company's sectors. The results extend the understanding of the role of intellectual capital in creating corporate value and building sustainable competitive advantages for companies in emerging economies, where different technological advancements may bring different implications for the valuation of intellectual capital.Abstrak:Penelitian ini bertujuan untuk menguji hubungan antara modal intelektual dan kinerja keuangan, pertumbuhan perusahaan, dan nilai pasar juga pada industri teknologi tinggi, industri berteknologi rendah, dan perusahaan telekomunikasi. Kontribusi lain dari penelitian ini adalah untuk menyelidiki apakah ada perbedaan modal intelektual antara masing-masing sektor perusahaan. Nilai Tambah Modal intelektual (VAICTM) metode oleh Pulic (1998, 1999, 2000, 2003) digunakan untuk memverifikasi pengaruh modal intelektual terhadap kinerja keuangan, pertumbuhan perusahaan, dan nilai pasar. Dengan menggunakan metode purposive sampling dalam periode 5 tahun dari 2010 hingga 2014, diperoleh 45 sampel industri teknologi tinggi, 185 sampel industri berteknologi rendah, dan 25 sampel perusahaan telekomunikasi. Partial Least Square (PLS) dan ANOVA satu arah digunakan dalam penelitian ini untuk menyelidiki penyebab empiris dari masing-masing variabel. Hasil analisis menunjukkan bahwa modal intelektual memiliki efek positif terhadap kinerja keuangan. Hasilnya juga mengungkapkan bahwa ada perbedaan modal intelektual dimasing-masing sektor perusahaan. Hasilnya memperluas pemahaman tentang peran modal intelektual dalam menciptakan nilai perusahaan dan membangun keunggulan kompetitif yang berkelanjutan bagi perusahaan di negara berkembang, di mana kemajuan teknologi yang berbeda dapat membawa implikasi yang berbeda untuk penilaian modal intelektual.